Approach toward a thermodynamic analysis on the drying and curing process of textile reinforcements for construction applications as a basis for continuous process control and optimization. (June 2021) - Hahn, Lars; Hong, Shichen; Treppe, Konrad; Zuben, Martin von; Rittner, Steffen; Beckmann, Michael; Cherif, Chokri
The development of energy-efficient textile manufacturing procedures is a crucial factor for cost reduction, potentially leading to the further establishment of technical textiles for industrial applications. In the textile sector, drying processes are responsible for the largest share of the total energy demand required by the manufacturing process. The performed investigations reveal that this fact also applies to infrared-based drying and curing procedures involved in the manufacturing of textile reinforcing structures for construction applications. The relationship between the temperature of the coated textile grid-like structure during drying and curing and infrared emitter power was analyzed and optimized. In addition, a thermodynamic concept was developed to replace the iterative setting of production parameters, such as infrared emitter power and machine speed. Thus, measurable process control parameters were identified that decisively influence the drying and curing process of textile reinforcements. The results of these investigations form the basis for procedural improvements (optimization variables: energy, time, and quality) as well as for the continuous monitoring of the drying and hardening process of textile reinforcements.